2020
DOI: 10.7554/elife.60645
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of mRNA and protein in single cells reveals post-transcriptional effects of genetic variation

Abstract: Trans-acting DNA variants may specifically affect mRNA or protein levels of genes located throughout the genome. However, prior work compared trans-acting loci mapped in separate studies, many of which had limited statistical power. Here, we developed a CRISPR-based system for simultaneous quantification of mRNA and protein of a given gene via dual fluorescent reporters in single, live cells of the yeast Saccharomyces cerevisiae. In large populations of recombinant cells from a cross between two genetically di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 115 publications
(195 reference statements)
1
51
0
Order By: Relevance
“…Similarly, our approach represents a viable strategy for mapping genetic effects on the degradation of individual proteins. Considerable discrepancies exist between genetic influences on gene expression at the mRNA and protein levels 42,71,73 . Many protein-specific QTLs could result from genetic effects on protein degradation, either through loci that alter the activity of protein degradation pathways or the degradation of individual proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, our approach represents a viable strategy for mapping genetic effects on the degradation of individual proteins. Considerable discrepancies exist between genetic influences on gene expression at the mRNA and protein levels 42,71,73 . Many protein-specific QTLs could result from genetic effects on protein degradation, either through loci that alter the activity of protein degradation pathways or the degradation of individual proteins.…”
Section: Discussionmentioning
confidence: 99%
“…between the strains can serve as markers in a genetic mapping experiment 43,44,71,73 .…”
Section: Yeast Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, recent work has shown that the number of trans -acting loci affecting gene expression throughout the genome may have been greatly underestimated due to linkage in experimental crosses with limited recombination ( Metzger and Wittkopp, 2019 ). These results paint an emerging picture of a highly polygenic architecture of gene expression variation, with dozens of trans -acting loci across the genome ( Albert et al, 2018 ; Albert et al, 2014b ; Brion et al, 2020 ; Metzger and Wittkopp, 2019 ), each of which may harbor multiple causal variants.…”
Section: Discussionmentioning
confidence: 99%